Preparation method of hydrophobic aerogel composite material with ultralow heat conductivity coefficient
Through sol-gel preparation and supercritical drying technology, silica aerogel composite materials with ultra-low thermal conductivity and good hydrophobic properties were prepared, which solved the problem of poor thermal insulation performance of existing materials and achieved a combination of efficient thermal insulation and temperature resistance.
Patent Information
- Application Number
- CN202411796205.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-18
AI Technical Summary
The existing silica aerogel composite materials have poor thermal insulation performance and are difficult to meet the high requirements of consumer electronic products for thermal conductivity, thermal insulation, thermal homogenization and other properties.
Through sol-gel preparation method, saturated absorbed silica aerogel sol is compounded with a glass fiber substrate, aged and dried in supercritical fluid CO2 to form an aerogel thermal insulation material with ultra-low thermal conductivity, good hydrophobic properties and high toughness.
It has achieved the preparation of aerogel thermal insulation materials with low thermal conductivity, excellent thermal insulation performance, high toughness and excellent hydrophobic properties, which solves the hydrophilicity and brittleness of traditional aerogel composite materials and is suitable for electronic products and other fields.
Smart Images

Figure CN119638364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel material preparation technology, and in particular to a method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material. Background Art
[0002] Silica aerogel is a structure-controllable lightweight nanoporous amorphous solid material with a porosity of 80% to 99.8%, a pore size of 1 to 100 nm, a high specific surface area of 200 to 1000 m2 / g, a low density range of 3 to 500 kg / m3, and a thermal conductivity of less than 0.013 W / mK at room temperature and pressure, which is lower than the thermal conductivity of still air (0.026 W / mK). It is currently the solid material with the lowest thermal conductivity. With the development of science and technology, consumer electronic products are becoming increasingly intelligent and lightweight, which means that the requirements for thermal conductivity, insulation, and heat distribution of electronic products are becoming higher and higher, especially for the thermal insulation, buffering, flame retardancy, lightness, energy saving and environmental protection of materials. It is urgent to develop a new type of high-efficiency thermal insulation material that combines lightness, good hydrophobicity and super thermal insulation performance. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material to solve the problem of poor thermal insulation performance of existing silica aerogel composite materials. A glass fiber substrate saturated with silica aerogel sol is placed in an aging liquid doped with a modifier for aging and dried with supercritical fluid CO2 through a sol-gel preparation method to form an aerogel insulation material with excellent thermal insulation performance, high toughness and excellent hydrophobic performance. The preparation method is simple to operate and can be produced continuously. At the same time, the aerogel structure is avoided from being destroyed to a certain extent, thereby ensuring the thermal insulation performance of the aerogel material.
[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material, the preparation method comprising the following steps:
[0005] (1) Ethyl silicate, 99% industrial ethanol, and deionized water are mixed uniformly in a volume ratio of (10-25): (120-150): (2-8), and a catalyst solution is added, wherein the amount of the catalyst added is 2%-10% of the total volume of the mixed solution in the above volume ratio, and stirred at room temperature for 10-40 minutes to obtain an aerogel mixed solution;
[0006] (2) impregnating the solution obtained in step (1) with a glass fiber substrate, and allowing to stand for 10-30 hours for a sol-gel reaction to form a glass fiber wet gel product;
[0007] (3) placing the glass fiber wet gel product obtained in step (2) in an aging liquid doped with a hydrophobic modifier for liquid aging modification, the aging modification time being 24-72 hours;
[0008] (4) placing the glass fiber wet gel product aged and modified in step (3) into supercritical drying to obtain a silica glass fiber aerogel insulation felt product.
[0009] As a preferred embodiment, the ethyl silicate described in step (1) is any one of ethyl orthosilicate 28, ethyl orthosilicate 40, and ethyl orthosilicate 50, or a mixture of any two or more thereof; the catalyst is any one of oxalic acid, hydrochloric acid, acetic acid, nitric acid, sulfuric acid, ammonia water, ammonium carbonate, and ammonium bicarbonate, or a mixture of any two or more thereof, and the molar ratio of the catalyst to the ethyl silicate is 1.5:0.01.
[0010] As a preferred embodiment, the glass fiber substrate in step (2) is short-fiber glass needle felt or long-fiber glass needle felt.
[0011] As a preferred embodiment, the wet gel aging temperature in step (3) is 20°C-50°C, and the aging time is 1-3 days; the aging modification liquid is one of silane coupling agent, siloxane compound, methyltriethoxysilane, polymethyltriethoxysilane, dimethyldiethoxysilane, or a mixture of any two or more thereof.
[0012] As a preferred embodiment, the supercritical drying temperature of the carbon dioxide gas described in step (4) is 80-180°C, and the drying pressure is 8-16 MPa; the flow rate of CO2 gas through the supercritical drying kettle is 900-1100 kg / h, and the drying time is 3-10 h.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] 1. The composite silica aerogel prepared by the present invention has good strength, high integrity, low thermal conductivity, and good hydrophobicity, thereby ensuring the thermal insulation and temperature resistance of the product, solving the problems of hydrophilicity and brittleness of traditional aerogel composite materials, and having good thermal resistance. It also provides convenience for market processing and application, and the ultra-low thermal conductivity also promotes the development of aerogel composite materials in the fields of electronic products. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The thermal conductivity test data of the silica glass fiber aerogel insulation felt prepared in Example 1;
[0016] Figure 2 This is the thermal insulation temperature difference curve of the silica glass fiber aerogel thermal insulation felt prepared in Example 1. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0019] See also Figure 1-2 As shown, the present invention provides the following technical solution: a method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material, the preparation method of which comprises the following steps:
[0020] (1) Ethyl silicate, 99% industrial ethanol, and deionized water are mixed uniformly in a volume ratio of (10-25): (120-150): (2-8), and a catalyst solution is added, wherein the amount of the catalyst added is 2%-10% of the total volume of the mixed solution in the above volume ratio, and stirred at room temperature for 10-40 minutes to obtain an aerogel mixed solution;
[0021] (2) impregnating the solution obtained in step (1) with a glass fiber substrate, and allowing to stand for 10-30 hours for a sol-gel reaction to form a glass fiber wet gel product;
[0022] (3) placing the glass fiber wet gel product obtained in step (2) in an aging liquid doped with a hydrophobic modifier for liquid aging modification, the aging modification time being 24-72 hours;
[0023] (4) placing the glass fiber wet gel product aged and modified in step (3) into supercritical drying to obtain a silica glass fiber aerogel insulation felt product.
[0024] Embodiment 1:
[0025] After 28% ethyl orthosilicate, 99% industrial ethanol and deionized water were uniformly mixed in a volume ratio of 15:130:4, the catalyst was added (the molar ratio of ethyl orthosilicate to the catalyst was 1.5:0.01), and the mixture was uniformly stirred at room temperature for 15 minutes. The mixture was poured into a container, and the aerogel mixed solution was impregnated with the short fiber glass needle felt substrate (the short fiber glass needle felt substrate had a thickness of 1.0 mm and a density of 135 kg / m 3), after standing for 12 hours, a sol-gel reaction was carried out to obtain a short fiber glass needle felt wet gel, the short fiber glass needle felt was immersed in an aging solution containing 99% industrial ethanol, silane coupling agent, and catalyst in a molar ratio of 8:1:0.006 and uniformly stirred for 30 hours, and then put into supercritical drying, the drying time was 4.5 hours, the drying temperature was 110°C, and the drying pressure was 10MPa to obtain a silica short fiber glass aerogel insulation felt, the thermal conductivity of the silica short fiber glass aerogel insulation felt at room temperature (25°C) was 0.013W / (m·K), the temperature resistance was 300°C-500°C, the compressive strength was 1.8-2Mpa, the compression rate was 45%-65%, the hydrophobicity was 98%, and the silica short fiber glass aerogel insulation felt product had high thermal insulation performance and good hydrophobic effect.
[0026] Embodiment 2:
[0027] After 40% ethyl orthosilicate, 99% industrial ethanol and deionized water were uniformly mixed in a volume ratio of 18:135:5, a catalyst was added (the molar ratio of ethyl orthosilicate to the catalyst was 1.5:0.01), and the mixture was uniformly stirred at room temperature for 20 minutes. The mixture was poured into a container, and the aerogel mixed solution was impregnated with the short fiber glass needle felt substrate (the short fiber glass needle felt substrate had a thickness of 0.7 mm and a density of 110 kg / m 3 ), after standing for 16 hours, a sol-gel reaction was carried out to obtain a short fiber glass needle felt wet gel, the short fiber glass needle felt wet gel was immersed in an aging solution containing 99% industrial ethanol, silane coupling agent, and catalyst in a molar ratio of 8:1:0.006 and uniformly stirred for 48 hours, and then put into supercritical drying, the drying time was 4 hours, the drying temperature was 120°C, and the drying pressure was 12MPa to obtain a silica short fiber glass aerogel insulation felt, the thermal conductivity of the silica short fiber glass aerogel insulation felt at room temperature (25°C) was 0.015W / (m·K), the temperature resistance was 300°C-500°C, the compressive strength was 1.8-2Mpa, the compression rate was 40%-60%, the hydrophobicity was 98%, and the silica short fiber glass aerogel insulation felt product had high thermal insulation performance and good hydrophobic effect.
[0028] Embodiment three:
[0029] After 40% ethyl orthosilicate, 99% industrial ethanol and deionized water were uniformly mixed in a volume ratio of 15:130:4, the catalyst was added (the molar ratio of ethyl orthosilicate to the catalyst was 1.5:0.01), stirred uniformly for 15 minutes at room temperature, poured into a container, and the aerogel mixed solution was impregnated with the short fiber glass needle felt substrate (the short fiber glass needle felt substrate had a thickness of 0.9 mm and a density of 117 kg / m 3), after standing for 12 hours, a sol-gel reaction was carried out to obtain a short fiber glass needle felt wet gel, the short fiber glass needle felt wet gel was immersed in an aging solution containing 99% industrial ethanol, silane coupling agent, and catalyst in a molar ratio of 8:1:0.006 and uniformly stirred for 30 hours, and then put into supercritical drying, the drying time was 4.5 hours, the drying temperature was 110°C, and the drying pressure was 10MPa to obtain a silica short fiber glass aerogel insulation felt, the thermal conductivity of the silica short fiber glass aerogel insulation felt at room temperature (25°C) was 0.013W / (m·K), the temperature resistance was 300°C-500°C, the strain compressive strength was 48%-65%, the compression rate was 1.8-2Mpa, the hydrophobicity was 99%, and the silica short fiber glass aerogel insulation felt product had high thermal insulation performance and good hydrophobic effect.
[0030] Embodiment 4:
[0031] After 40% ethyl orthosilicate, 99% industrial ethanol and deionized water were uniformly mixed in a volume ratio of 18:135:5, a catalyst was added (the molar ratio of ethyl orthosilicate to the catalyst was 1.5:0.01), and the mixture was uniformly stirred at room temperature for 20 minutes. The mixture was poured into a container, and the aerogel mixed solution was impregnated with the short fiber glass needle felt substrate (the short fiber glass needle felt substrate had a thickness of 1.6 mm and a density of 135 kg / m 3 ), after standing for 16 hours, a sol-gel reaction was carried out to obtain a short fiber glass needle felt wet gel, the short fiber glass needle felt wet gel was immersed in an aging solution containing 99% industrial ethanol, silane coupling agent, and catalyst in a molar ratio of 8:1:0.006 and uniformly stirred for 48 hours, and then put into supercritical drying, the drying time was 4 hours, the drying temperature was 120°C, and the drying pressure was 12MPa to obtain a silica short fiber glass aerogel insulation felt, the thermal conductivity of the silica short fiber glass aerogel insulation felt at room temperature (25°C) was 0.012W / (m·K), the temperature resistance was 300°C-500°C, the compressive strength was 1.8-2Mpa, the compression rate was 40%-50%, the hydrophobicity was 99%, and the silica short fiber glass aerogel insulation felt product had high thermal insulation performance and good hydrophobic effect.
[0032] Embodiment five:
[0033] After 50% ethyl orthosilicate, 99% industrial ethanol and deionized water were uniformly mixed in a volume ratio of 15:130:4, the catalyst was added (the molar ratio of 50% ethyl orthosilicate to the catalyst was 1.8:0.02), and the mixture was uniformly stirred at room temperature for 20 minutes. The mixture was poured into a container, and the aerogel mixed solution was impregnated with the short fiber glass needle felt substrate (the short fiber glass needle felt substrate had a thickness of 0.9 mm and a density of 117 kg / m 3), after standing for 18 hours, a sol-gel reaction was carried out to obtain a short fiber glass needle felt wet gel, the short fiber glass needle felt wet gel was immersed in an aging solution containing 99% industrial ethanol, silane coupling agent, and catalyst in a molar ratio of 10:2:0.01 and uniformly stirred for 48 hours, and then put into supercritical drying, the drying time was 4.5 hours, the drying temperature was 130°C, and the drying pressure was 13MPa, to obtain a silica short fiber glass aerogel insulation felt, the silica short fiber glass aerogel insulation felt has a thermal conductivity of 0.016W / (m·K) at room temperature (25°C), a temperature resistance of 280°C-400°C, a strain compressive strength of 62%-72%, a compression rate of 1.8-2Mpa, and a hydrophobicity of 98%. The silica short fiber glass aerogel insulation felt product has high thermal insulation performance and good hydrophobic effect.
[0034] Embodiment six:
[0035] After 50% ethyl orthosilicate, 99% industrial ethanol and deionized water were uniformly mixed in a volume ratio of 18:135:5, the catalyst was added (the molar ratio of 50% ethyl orthosilicate to the catalyst was 1.5:0.01), and the mixture was uniformly stirred at room temperature for 30 minutes. The mixture was poured into a container, and the aerogel mixed solution was impregnated with the short fiber glass needle felt substrate (the short fiber glass needle felt substrate had a thickness of 0.9 mm and a density of 117 kg / m 3 ), after standing for 16 hours, a sol-gel reaction was carried out to obtain a short fiber glass needle felt wet gel, the short fiber glass needle felt wet gel was immersed in an aging solution containing 99% industrial ethanol, silane coupling agent, and catalyst in a molar ratio of 8:1:0.006 and uniformly stirred for 48 hours, and then put into supercritical drying, the drying time was 4 hours, the drying temperature was 120°C, and the drying pressure was 12MPa to obtain a silica short fiber glass aerogel insulation felt, the thermal conductivity of the silica short fiber glass aerogel insulation felt at room temperature (25°C) was 0.017W / (m·K), the temperature resistance was 300°C-400°C, the compressive strength was 1.8-2Mpa, the compression rate was 65%-75%, the hydrophobicity was 98%, and the silica short fiber glass aerogel insulation felt product had high thermal insulation performance and good hydrophobic effect.
[0036] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material, characterized in that: The preparation method comprises the following steps: (1) Ethyl silicate, 99% industrial ethanol, and deionized water are mixed uniformly in a volume ratio of (10-25): (120-150): (2-8), and a catalyst solution is added, wherein the amount of the catalyst added is 2%-10% of the total volume of the mixed solution in the above volume ratio, and stirred at room temperature for 10-40 minutes to obtain an aerogel mixed solution; (2) impregnating the solution obtained in step (1) with a glass fiber substrate, and allowing to stand for 10-30 hours for a sol-gel reaction to form a glass fiber wet gel product; (3) placing the glass fiber wet gel product obtained in step (2) in an aging liquid doped with a hydrophobic modifier for liquid aging modification, the aging modification time being 24-72 hours; (4) placing the glass fiber wet gel product aged and modified in step (3) into supercritical drying to obtain a silica glass fiber aerogel insulation felt product.
2. The method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material according to claim 1, characterized in that: The ethyl silicate described in step (1) is any one of ethyl orthosilicate 28, ethyl orthosilicate 40, and ethyl orthosilicate 50, or a mixture of any two or more thereof; the catalyst is any one of oxalic acid, hydrochloric acid, acetic acid, nitric acid, sulfuric acid, ammonia water, ammonium carbonate, and ammonium bicarbonate, or a mixture of any two or more thereof, and the molar ratio of the catalyst to the ethyl silicate is 1.5:0.
01.
3. The method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material according to claim 1, characterized in that: The glass fiber substrate described in step (2) is short fiber glass needle felt or long fiber glass needle felt.
4. The method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material according to claim 1, characterized in that: The wet gel aging temperature in step (3) is 20°C-50°C, and the aging time is 1-3 days; the aging modification liquid is one of silane coupling agent, siloxane compound, methyltriethoxysilane, polymethyltriethoxysilane, dimethyldiethoxysilane, or a mixture of any two or more thereof.
5. The method for preparing an ultra-low thermal conductivity hydrophobic aerogel composite material according to claim 1, characterized in that: The supercritical drying temperature of the carbon dioxide gas described in step (4) is 80-180°C, and the drying pressure is 8-16MPa; the flow rate of CO2 gas through the supercritical drying kettle is 900-1100kg / h, and the drying time is 3-10h.
Citation Information
Cited By
Preparation method of ultrahigh-hydrophobicity low-density SiO2 aerogel particles
CN120793944A
High-temperature-resistant thermal-insulating aerogel composite material, preparation method therefor and use thereof
WO2026194326A1